Educating Cooperative members to Increase Its Values (A study on the Members Education in KSU Makmur Sejati Malang and Koperasi Kredit Sangosay, Ngada Nusa Tenggara Timur) - Sutrisno, Sutrisno (Fakultas Ekonomi, Universitas Negeri Semarang, 2018)
The aims of this study to educate themembers on comprehension about enhancement cooperative values (self-help, self-responsibility, democracy, equality, equity, solidarity) at the KSU Makmur Sejati Malang and Credit cooperative of Sangosay Ngada,East Nusa Tenggara. Informants consisted of members, organizational devices (Management and Supervisory) and a support device in the cooperative organization. Sampling technique used is purposive sampling. Aspects of a method and inductive analysis are considered in the study with a qualitative approach. Informative cooperative devices (Management and Supervisors) and employees role as the parts of triangulation analysis. The growth of an understanding of the values of the cooperative members through education, both directly and indirectly. KSU Makmur Sejati and Sangosay Credit Cooperative considers that the annual meeting of members turns into a great media to instil the value of the cooperative. The presence in the meeting members gives pride for the members. Pride grows because success is the success of the cooperative members. Self-help value grows on this aspect.